Utilizing the Context of Batik Parang Teja in Developing Teaching Materials Supported by Desmos Classroom on Translation and Reflection Topic - Yulianingrum, Margareta Elvina; Putra, Aloisius Fieri Dharma; Nugraha, Adhi Surya (Edumatika, 2024)
Integrating the culture around students environtment into mathematics learning can make learning more innovative, interesting, contextual and meaningful. This research aims to develop translation and reflection teaching materials assisted by Desmos Classroom by utilizing the Batik Parang Teja context. Teaching materials were developed using the ADDIE development model. The research stages include conducting literature review, designing teaching materials, improving its quality based on expert input, applying teaching materials in classroom, and evaluating the quality of the teaching materials developed. The data of the product quality are collected through validation sheets by experts. Based on experts judgement, the Desmos Classroom-assisted teaching materials developed being suitable for use in mathematics learning, especially translation and reflection topic.